Iowa RBA, December 14, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Iowa RBA for December 14, 1998. Highlights include Snowy Owl, Eurasian Collared Dove, Red-throated Loon, and Western Grebe. Includes notes for updates for December 16, and December 18. Epson - sheet feed/flatbed